Pengaruh PENGARUH PROJECT-BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V DI SDN KALOY - Khairunnisa; Fajar Solidman Larosa; Jelita Panjaitan (Jurnal Pendidikan Dasar, 2026)
Critical thinking is an essential skill that needs to be developed in elementary education to prepare students for academic and real-life challenges. However, learning activities in elementary schools are often dominated by teacher-centered instruction, which limits students’ opportunities to engage in higher-order thinking. This study aimed to examine the effect of Project-Based Learning on the critical thinking skills of fifth-grade students in Science learning, specifically on the topic of ecosystems, at SDN Kaloy.. The research employed a quasi-experimental design using a pretest–posttest control group design. The participants consisted of two fifth-grade classes, one assigned as the experimental group and the other as the control group. The experimental group was taught using Project-Based Learning, while the control group received Direct Instruction. Data were collected through a critical thinking skills test administered before and after the learning intervention. The collected data were analyzed using an independent sample t-test after meeting the assumptions of normality and homogeneity. The results showed that students in the experimental group achieved higher posttest scores in critical thinking skills compared to students in the control group. Statistical analysis indicated a significant difference between the two groups, demonstrating that Project-Based Learning had a positive and significant effect on students’ critical thinking skills. These findings indicate that Project-Based Learning is an effective instructional approach for enhancing critical thinking skills in elementary school students and can be implemented as an alternative learning model to support active and meaningful learning.